Florida Blueberry Integrated Pest Management Guide - Jeffrey G. Williamson; Philip F. Harmon; Oscar E. Liburd (EDIS)
HS-1156 is a 35-page illustrated guide adapted for Florida from the Southeast Regional Blueberry Integrated Management Guide by Jeffrey G. Williamson, Philip F. Harmon, and Oscar E. Liburd. Primarily tabular in format, it also includes links to additional resources, text descriptions of key pests by stages of flower bud development, and an illustrated guide to recognized stages. Published by the UF Department of Horticultural Science, March 2008.